Cerebrospinal Fluid Pterins, Pterin-Dependent Neurotransmitters, and Mortality in Pediatric Cerebral Malaria. (22nd February 2021) - Rubach, Matthew P; Mukemba, Jackson P; Florence, Salvatore M; Lopansri, Bert K; Hyland, Keith; Simmons, Ryan A; Langelier, Charles; Nakielny, Sara; DeRisi, Joseph L; Yeo, Tsin W; Anstey, Nicholas M; Weinberg, J Brice; et al.
Abstract: Background: Cerebral malaria (CM) pathogenesis remains incompletely understood. Having shown low systemic levels of tetrahydrobiopterin (BH4 ), an enzymatic cofactor for neurotransmitter synthesis, we hypothesized that BH4 and BH4 -dependent neurotransmitters would likewise be low in cerebrospinal fluid (CSF) in CM. Methods: We prospectively enrolled Tanzanian children with CM and children with nonmalaria central nervous system conditions (NMCs). We measured CSF levels of BH4, neopterin, and BH4 -dependent neurotransmitter metabolites, 3- O -methyldopa, homovanillic acid, and 5-hydroxyindoleacetate, and we derived age-adjusted z-scores using published reference ranges. Results: Cerebrospinal fluid BH4 was elevated in CM (n = 49) compared with NMC (n = 51) (z-score 0.75 vs −0.08; P  < .001). Neopterin was increased in CM (z-score 4.05 vs 0.09; P  < .001), and a cutoff at the upper limit of normal (60 nmol/L) was 100% sensitive for CM. Neurotransmitter metabolite levels were overall preserved. A higher CSF BH4 /BH2 ratio was associated with increased odds of survival (odds ratio, 2.94; 95% confidence interval, 1.03–8.33; P  = .043). Conclusion: Despite low systemic BH4, CSF BH4 was elevated and associated with increased odds of survival in CM. Coma in malaria is not explained by deficiency of BH4 -dependent neurotransmitters. Elevated CSF neopterin was 100% sensitive for CM diagnosis and warrants further assessment of its clinical utility for ruling out CM in malaria-endemic areas. Abstract : We hypothesized that central nervous system (CNS) tetrahydrobiopterin deficiency contributes to the pathogenesis of cerebral malaria. Instead, we found cerebrospinal fluid tetrahydrobiopterin was elevated in cerebral malaria relative to other CNS diseases, and increase in tetrahydrobiopterin was associated with survival.